International diversification, reallocation, and the labor share - Joel M. David; Romain Rancière; David Zeke (Federal Reserve Bank of Chicago, 2023)
How does growing international financial diversification affect firm-level and aggregate labor shares? We study this question using a novel framework of firm labor choice in the face of aggregate risk. The theory implies a cross-section of labor risk premia and labor shares that appear as markups in firm-level data. International risk sharing leads to a reallocation of labor towards riskier/low labor share firms alongside a rise in within-firm labor shares, matching key micro-level facts. We use cross-country firm-level data to document a number of empirical patterns consistent with the theory, namely: (i) riskier firms have lower labor shares and (ii) international financial diversification is associated with a reallocation towards risky/low labor share firms. Our estimates suggest the reallocation effect has dominated the within effect in recent decades; on net, increased financial integration has reduced the corporate labor share in the US by about 2.5 percentage points, roughly one-third of the total decline since the 1970s.
Keywords: 330; Internationale Geschäftsbeziehungen; Internationale Faktormobilität; Kapitalmobilität; Internationale Unternehmensfinanzierung; Lohnquote; Welt